2012
DOI: 10.1097/scs.0b013e31825e60ae
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Major and Minor Brain Injuries in Facial Fractures

Abstract: Facial fractures are often associated with brain injury. A high level of suspicion is warranted for minor traumatic brain injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 13 publications
3
16
0
1
Order By: Relevance
“…There is a controversy in the literature about the association of THI with MFF with some studies reporting that the percentage ranged from 5.4 to 45.5%, while in other studies the percentage can reach up to 86% in more serious MFF . Due to the close anatomical proximity of the maxillofacial bones and the cranium, it is common that patients with MFF are at increased risk of, and suffer from, THI simultaneously which can lead to primary or secondary brain damage in case of a missed or late diagnosis in such cases …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a controversy in the literature about the association of THI with MFF with some studies reporting that the percentage ranged from 5.4 to 45.5%, while in other studies the percentage can reach up to 86% in more serious MFF . Due to the close anatomical proximity of the maxillofacial bones and the cranium, it is common that patients with MFF are at increased risk of, and suffer from, THI simultaneously which can lead to primary or secondary brain damage in case of a missed or late diagnosis in such cases …”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] Due to the close anatomical proximity of the maxillofacial bones and the cranium, it is common that patients with MFF are at increased risk of, and suffer from, THI simultaneously which can lead to primary or secondary brain damage in case of a missed or late diagnosis in such cases. 2,12,13 Globally, THI will exceed many other diseases as the main cause of disability and death by the year 2020 according to the WHO as it is a significant public health problem. It impairs brain function and it often results in negative long-term or permanent physical, cognitive, behavioural and emotional changes.…”
Section: Introductionmentioning
confidence: 99%
“…The overriding parts of disseminated studies have shown high proportion in adolescent. 18 In current study, congregation in the age of 20-39 years was the mainly subjective of maxillofacial injury but in a equivalent study, the author told similar characteristics, with the a good number as often as probable predisposed age congregation being 21-30 years. 19,20,21 The etiology of maxillofacial & concomitant injuries in our study results clearly indicated RTA was the widespread causative factor followed by assaults, which were similar with the studies conducted in different parts of world.…”
Section: Resultsmentioning
confidence: 67%
“…As shown in With respect to associated injuries, a sum of 48 patients introduced head injuries and other concomitant injuries as described in Figure- 17 and study conducted by Grant Al clearly indicated Incidence of brain injury was 67% overall which is not similar with results of our study. 18 It is hard to separate the mortality & dreadfulness of maxillofacial fractures associated with it. The overriding parts of disseminated studies have shown high proportion in adolescent.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies also show that fractures in the facial area have led to the brain and spine cord problems. The study of Grant et al [9], which conducted in the US, determined that brain damages in people with facial fractures were generally 67 percent. Hugh et al [10] in a study showed that the incidence of brain damage associated with facial fractures is estimated to be 17.5 percent.…”
Section: Introductionmentioning
confidence: 99%